A CLINICAL CASE OF ABDOMINAL PREGNANCY WITH PRESERVATION OF THE WOMAN’S REPRODUCTIVE POTENTIAL - Николаева, Любовь Борисовна; Лебединская, Лилия Фаритовна; Гордеева, Елена Сергеевна; Стрюк, Ирина Юрьевна; Баранов, Владимир Алексеевич; Мозес, Вадим Гельевич (Medicine in Kuzbass, 2025)
Abdominal pregnancy (AP) is a pregnancy in which the fertilized egg (embryo) implants outside the uterine cavity (in the omentum, peritoneum, or on the surface of abdominal organs) and is a rare form of ectopic pregnancy, accounting for 0.3-0.4% of all extrauterine pregnancies. Despite its rarity, AP is characterized by massive bleeding, which significantly increases the risk of mortality compared to tubal (7-8 times higher) and uterine (90 times higher) pregnancies. Risk factors for abdominal pregnancy include pathological changes in the reproductive system, age, stress, and endocrine disorders [1-4]. To date, clinical and ultrasound signs of AP remain insufficiently reliable, and the timeliness and accuracy of correct diagnosis do not exceed 50% [2-5]. According to domestic and foreign literature, in most cases, AP is confirmed only intraoperatively, due to the lack of a standardized diagnostic, management, and treatment algorithm for this type of pregnancy [3-5]. We present a clinical case of abdominal pregnancy, confirmed intraoperatively, with organ-preserving surgical intervention and preservation of the woman’s reproductive potential.